THE INFLUENCE OF WORKING CAPITAL TURN OVER , CASH TURN OVER AND INVENTORY TURN OVER TO PROFITABILITY ON PT. MULIA KEKAL ABADI IN 2014-2016 PERIOD - Rukmana Sari, Ike; Theresia, Theresia; Clara Amanda, Charisa (EDUTECH CONSULTANT, 2019)
The Method used in this study is quantitative research. Collection data used documentation technique and secondary data collection from financial statements of PT. Mulia Kekal Abadi in 2014 – 2016 period. The amount of sample come from 36 observation during 3 years research. The analisys model in this study uses multiple linear Regression with soft program named SPSS. The data testing performed with classical assumption test, F test and t test. The conclusion of this study partially Cash Turn Over had positive influence and significant to Profitability, meanwhile Working Capital Turn Over and Inventory Turn Over had no influences to Profitability. In the other hands, Working Capital Turn Over, Cash Turn Over and Inventory Turn Over simultanouesly had significatnt influence to Profitability on PT. Mulia Kekal Abadi in period 2014-2016. The testing result shows that coefisien determation (R square) R2 is 38,1%. The value of R2 is 38,1% means in every profitability variable variation, 38,1% caused by changing variable variation of Working Capital Turn Over, Cash Turn Over and Inventory Turn Over. The residual value 61,9% caused by other variable like working capital; sales; account receivable; debt which is not explained in this study.